Introduction of The Green Concept in Financial Report Recording to Ulos Weaving Actors - Sidabutar, Rimbun C D; Sinurat, Mangasa; Telaumbanua, Billy Anugerah Sosaraya (Borneo Research and Education Center, 2025)
In a globalized era of uncertainty, sustainability and environmental responsibility have become a key focus for business and society. Relevant parties must take immediate action in response to critical issues such as climate change, environmental degradation, and the need for sustainable resources. Private and public sector organizations are expected to pursue financial returns and implement environmentally responsible business practices amidst the complexity of such issues. The company's concern for the environment is very important, considering that the environment and society have been exposed to many negative influences due to the activities carried out by the company. These negative influences arise from the activities of companies, especially in exploiting natural resources as the main material and in the production process. This results in pollution, poisoning, and noise, which have disrupted people's lives in the short and long term. Implementing this community service first involved conducting preliminary observations to determine the conditions owned by weaving business actors. Observations were made after a letter of request for assistance was received from the ulos weaving partners of Sigaol Timur Village, Uluan District, Toba Regency. The service was implemented on 15 June 2024 in Sigaol Village, Uluan District, Toba Regency. The weaver group mostly uses yarn with chemical dyes because it produces brighter colors than natural dyes. Customers prefer this bright color. Chemically dyed yarns can be used directly as weaving materials. At the same time, naturally dyed yarns require a longer process and the weaver's creativity to combine several types of plants to produce a color blend. Chemical dyes are mostly used to meet market demand, so Ulos is bright. Weavers became interested in increasing their knowledge of yarn dyeing and waste management. They started to record how much liquid waste is disposed of, including the amount of waste left over from making natural color yarn, recognizing environmental costs that can be recorded as production costs.